Current perspectives on phytoestrogens: A boon or a caution in today's era - RAVAL A.A., (International Journal of Pharma and Bio Sciences, 2017)
Phytoestrogens are plant derived compounds found in a wide variety of foods, most notably soy. An array of health benefits including a lowered risk of osteoporosis, heart disease, breast cancer, and menopausal symptoms, are frequently attributed to phytoestrogens but many are also considered endocrine disruptors, indicating that they have the potential to cause adverse health effects as well. This review describes some of the studies done and experiments performed to evaluate the effectiveness of phytoestrogens as friends or foes. Still most of the studies done are confusing whether women should consume these phytoestrogens for the health benefit so not. Whether phytoestrogens consumption can be linked to decreasing risk of breast cancer or not and if yes what should be the proportion to attain maximum benefit are still to be evaluated.